การออกแบบและสร้างแหล่งกำเนิดไฟฟ้ากระแสสลับความถี่สูงที่เป็นแหล่งกำลังของเครื่องตัดจี้ไฟฟ้า - จิตติยา ธนะสินธราทิพย์ (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
This thesis presents a design and implement of a high frequency generator for an electrosurgical unit by using half-bridge inverter series resonant parallel load. In normal operating conditions, load resistance of an electrosurgical unit can vary from open circuit to short circuit. To design a resonant inverter operating over an extreme load range, simple circuit equations for circuit analysis and design are indispensable. Fundamental frequency approximation allows sinusoidal steady-state analytical technique to be applied to the analysis and design of resonant inverter according to specification and restriction of electrosurgical unit. In order to avoid false turn-on and high output voltage over-shoot, gate drive circuit was analyzed, and circuit parameters as well as gate drive waveform were carefully designed. In the design and implement of high frequency transformer and inductor, both skin effect and proximity effect were taken into consideration to improve efficiency.